2007
DOI: 10.1104/pp.107.098723
|View full text |Cite
|
Sign up to set email alerts
|

Combined Transcriptome and Proteome Analysis Identifies Pathways and Markers Associated with the Establishment of Rapeseed Microspore-Derived Embryo Development

Abstract: Microspore-derived embryo (MDE) cultures are used as a model system to study plant cell totipotency and as an in vitro system to study embryo development. We characterized and compared the transcriptome and proteome of rapeseed (Brassica napus) MDEs from the few-celled stage to the globular/heart stage using two MDE culture systems: conventional cultures in which MDEs initially develop as unorganized clusters that usually lack a suspensor, and a novel suspensor-bearing embryo culture system in which the embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
141
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(151 citation statements)
references
References 72 publications
3
141
0
7
Order By: Relevance
“…The hypothesis has been put forward ( _ Zur et al 2014), claiming that the effectiveness of ME in triticale anther cultures depends on both cell tolerance to/defence ability against oxidative stress and ROS-induced signal transduction associated with the stress treatment used for microspore reprogramming. Similarly to our study, one of the antioxidative enzyme-L-ascorbate peroxidase 1 (spot no 9) was accumulated after ME-inducing treatment in maize and rapeseed (Joosen et al 2007;Cordewener et al 2009;Uváčková et al 2012). Its role can be more complex as in various plant cell culture systems high ascorbate levels stimulate cell division (de Pinto et al 1999).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The hypothesis has been put forward ( _ Zur et al 2014), claiming that the effectiveness of ME in triticale anther cultures depends on both cell tolerance to/defence ability against oxidative stress and ROS-induced signal transduction associated with the stress treatment used for microspore reprogramming. Similarly to our study, one of the antioxidative enzyme-L-ascorbate peroxidase 1 (spot no 9) was accumulated after ME-inducing treatment in maize and rapeseed (Joosen et al 2007;Cordewener et al 2009;Uváčková et al 2012). Its role can be more complex as in various plant cell culture systems high ascorbate levels stimulate cell division (de Pinto et al 1999).…”
Section: Discussionsupporting
confidence: 81%
“…Microspore reprogramming not only implies the expression of an embryogenic program, but also a stress-related cellular response and a repression of the gametophytic program. Numerous studies focused on searching for the gene(s) responsible for efficient ME induction with the use of model plant species: rapeseed (Joosen et al 2007), wheat (Sánchez-Díaz et al 2013) and barley (Muñoz-Amatriaín et al 2009). The first report for molecular regulation of ME in triticale was published recently ( _ Zur et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Due to these advantages, it is not surprising that the B. napus MDE culture system has been extensively utilized to investigate anatomical, physiological, and molecular events occurring during embryo development in vitro (reviewed in Yeung 2002;Boutilier et al 2005). Recent transcriptome and proteome analyses have focused on the molecular events delineating the induction of microspore embryogenesis, that is the initial transition from gametophytic to embryonic cell state (Joosen et al 2007;Malik et al 2007). Both studies have revealed the existence of robust markers and pathways associated with the early phases of embryo development.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression proWling is a powerful tool for dissecting the molecular mechanisms of relevant developmental processes, including embryogenesis. Over the past few years cDNA microarray studies have revealed the existence of transcript patterns associated with embryo development in both angiosperms (Girke et al 2000;Thibaud-Nissen et al 2003;Joosen et al 2007;Malik et al 2007) and gymnosperms (Stasolla et al 2003(Stasolla et al , 2004b. Most importantly, these studies have revealed the existence of key genes able to aVect the embryogenic process if their expression level is experimentally altered (Tahir et al 2006;).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies using macro-and microarray technology have been used to further understanding of the molecular processes that take place in embryogenic microspores and microspore-derived embryos in Brassica (Pauls et al 2006, Joosen et al 2007, Malik et al 2007. Although microspore embryogenesis is highly dependent on the species, genotype, stress pretreatment and culture media, utilization of microarray techniques is providing new insights into the molecular mechanisms that control microspore embryogenesis.…”
Section: Discussionmentioning
confidence: 99%